FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN KERJA KARYAWAN BAGIAN SEWING PT. HOP LUN INDONESIA - Siti Khoirus Sa’adah; Edy Dwi Kurniati; Fajar Suryatama (BISECER (Business Economic Entrepreneurship), 2022)
Employees who are satisfied with their work will perform well. Job satisfaction is basically influenced by many factors such as compensation, career development, leadership style or others. Job satisfaction is a problem that is quite interesting and important because it has proven to be of great benefit to the interests of individuals, companies or organizations. Job satisfaction of employees of the sewing section of PT. HOP LUN INDONESIA can be seen from the increase in employee absenteeism. This study aims to analyze the effect of compensation, career development, and leadership style variables on job satisfaction. This study uses quantitative methods. The population in this study were all employees of the sewing section of PT. HOP LUN INDONESIA numbered 216 people. The sampling technique used is simple random sampling method, and the number of samples is 140 people. The data collection method uses Google form, while the data analysis techniques are validity test, reliability test, correlation analysis, regression analysis, t test, F test, coefficient of determination test. The results showed that simultaneously and partially, compensation, career development, and leadership style had an effect on employee job satisfaction.